(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Khaya grandifoliola C. DC. (Meliaceae) is exploited as a popular antimalarial herbal medicine in Nigeria, externally in treating skin diseases, and to enhance libido. Objectives: This study evaluates the aphrodisiac potential of K. grandifoliola leaf in male Wistar rats. Materials and methods: Aphrodisiac property was determined by oral administration of graded doses: 100, 250 and 1000 mg/kg of crude methanol (MeOH) extract of K. grandifoliola leaf, and 100 and 200 mg/kg each of aqueous (AQ) and dichloromethane (DCM) fractions to male rats using standard procedure. Sildenafil citrate and distilled water served as positive and negative controls, respectively. Sexual behavioural parameters like mounting, intromission and ejaculatory frequencies and latencies were recorded on day 7. Anti-lipid peroxidation effect and serum testosterone concentrations were also monitored. Results: From the sexual behavioural study, MeOH extract of the leaf was active and significantly increased mount and ejaculatory frequencies, and decreased mount and ejaculatory latencies in a dose dependent manner, but had no effect on intromission latency and intromission frequency. Both AQ and DCM fractions were more active than extract, comparable to Sildenafil citrate, but DCM fraction was comparatively more active. Testosterone concentrations were also increased dose-dependently by all tested agents, but DCM fraction was the most active and comparable to Sildenafil citrate. Only DCM fraction significantly inhibited lipid peroxidation but was not comparable to Vitamin E. Conclusion: From all indications, MeOH extract and fractions of K. grandifoliola leaf which increased serum testosterone and sexual behavioural indices has potential for improving sexual dysfunction in males, and the more active DCM fraction qualifies for further phytochemical investigation to isolate active compounds. These findings therefore justify the acclaimed local use of K. grandifoliola leaf in treating male infertility.